Quantification and removal of volatile sulfur compounds (VSCS) in atmospheric emissions in large (Petro) chemical complexes in different countries of America and Europe (2022)
The present research was focused on the determination and removal of sulfur-containing compounds in industrial emissions of liquefied petroleum gas purification processes in petrochemical plants located in the USA, Brazil, Colombia, Spain, and Italy. For the analysis of volatile sulfur compounds (VSCs), an improved analytical methodology was implemented. The performance of the method was evaluated for eight VSCs in a linear dynamic range between 0.1 and 50 ppm. The concentrations of the eight VSCs in the deethanizer affluents ranged from 11 to 49 ppm for all the studied plants, which exceed the limits specified by institutions and administrations in occupational health and safety. The concentrations of the eight VSCs in the splitter affluents were lower than 4 ppm for all the considered plants. The emissions from each column depended upon its operating rate, with the highest concentrations estimated at 45 TM kg−1 and the lowest ones at 25 TM kg−1. A zeolite-packed prototype column was fitted at the outlet of the splitter and deethanizer columns to reduce the environmental effect of the examined VSCs. This technique was verified and put into practice on an industrial scale, obtaining VSC removal percentages of between 85 and 91%.